ENO3 Inhibits Growth and Metastasis of Hepatocellular Carcinoma via Wnt/β-Catenin Signaling Pathway - Cui, Honglei; Guo, Danfeng; Zhang, Xiaodan; Zhu, Yaohua; Wang, Zhihui; Jin, Yang; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Cell and Developmental Biology, 2021)
β-enolase（ENO3）, a metalloenzyme that functions during glycolysis, has been revealed ectopic expression in different cancers. However, the role and underlying regulatory mechanisms of ENO3 in hepatocellular carcinoma (HCC) remain elusive. Here we found ENO3 was significantly downregulated in human HCC tissues compared with those in noncancerous tissues. Moreover, low expression of ENO3 was associated with poor prognosis of HCC patients. Overexpression of ENO3 suppressed proliferation, migration, and invasion of HCC cells both in vitro and in vivo, whereas knockdown of ENO3 led to the opposite effect. In addition, we demonstrated ENO3 repressed the epithelial-mesenchymal transition (EMT) process with its marker alterations. Mechanistic study revealed that ENO3 inhibited the Wnt/β-catenin signaling pathway, which subsequently modulated the expression of its target genes relating to the proliferation and metastasis capacity of HCC cells. Taken together, our study uncovered that ENO3 acted as a tumor suppressor in the progression of HCC and implied ENO3 as a promising candidate for HCC treatment.